Suppression of Trichothecene-Mediated Immune Response by the Fusarium Secondary Metabolite Butenolide in Human Colon Epithelial Cells - Woelflingseder, Lydia; Adam, Gerhard; Marko, Doris (Frontiers in Nutrition, 2020)
Butenolide (BUT, 4-acetamido-4-hydroxy-2-butenoic acid gamma-lactone) is a secondary metabolite produced by several Fusarium species and is co-produced with the major trichothecene mycotoxin deoxynivalenol (DON) on cereal grains throughout the world. BUT has low acute toxicity and only very limited occurrence and exposure data are available. The intestinal epithelium represents the first physiological barrier against food contaminants. We aimed to elucidate the intestinal inflammatory response of the human, non cancer epithelial HCEC 1CT cells to BUT and to characterize potential combinatory interactions with co occurring trichothecenes, such as DON and NX 3. Using a reporter gene approach, BUT (≥5 µM, 20 h) was found to decrease lipopolysaccharide (LPS; 10 ng/mL) induced nuclear factor kappa B (NF κB) activation in a dose-dependent manner, and in combinatory treatments represses trichothecene induced enhancement of this important inflammatory pathway. Analyzing transcription and secretion levels of NF κB dependent, pro inflammatory cytokines, revealed a significant down-regulation of IL 1, IL-6 and TNF  in IL 1 stimulated (25 ng/mL) HCEC 1CT cells after BUT exposure (10 µM). Trichothecene induced expression of pro inflammatory cytokines by the presence of 1 µM DON or NX 3 was substantially suppressed in the presence of 10 µM BUT. The emerging mycotoxin BUT has the ability to suppress NF κB induced intestinal inflammatory response mechanisms and to modulate substantially the immune responsiveness of HCEC 1CT cells after trichothecene treatment. Our results suggest that BUT, present in naturally occurring mixtures of Fusarium fungal metabolites, should be increasingly monitored, and the mechanism of inhibition of NF-κB that might affect the pathogenesis or progression of intestinal inflammatory disorders, should be further investigated.